Engaging in Creativity Broadens Attentional Scope - Wronska, Marta K.; Kolańczyk, Alina; Nijstad, Bernard A. (Frontiers in Psychology, 2018)
Previous studies have shown that creativity is enhanced by a broad attentional scope, defined as an ability to utilize peripheral stimuli and process information globally. We propose that the reverse relationship also holds, and that breadth of attention also is a consequence of engaging in a creative activity. In Study 1, participants showed increased breadth of attention in a visual scanning task after performing a divergent thinking task as opposed to an analytic thinking task. In Study 2, participants recognized peripheral stimuli displayed during the task better after performing a divergent thinking task as compared to an analytic task, whereas recognition performance of participants performing a task that involves a mix of divergent and analytic thinking (the Remote Associates Test) fell in between. Additionally, in Study 2 (but not in Study 1), breadth of attention was positively correlated with performance in a divergent thinking task, but not with performance in an analytic thinking task. Our findings suggest that the adjustment of the cognitive system to task demands manifests at a very basic, perceptual level, through changes in the breadth of visual attention. This paper contributes a new, motivational perspective on attentional breadth and discusses it as a result of adjusting cognitive processing to the task requirements, which contributes to effective self-regulation.